DNA Damage-Induced Cell Cycle Regulation and Function of Novel Chk2 Phosphoresidues - Buscemi, Giacomo (American Society for Microbiology, 2006)
Chk2 kinase is activated by DNA damage to regulate cell cycle arrest, DNA repair, and apoptosis. Phosphorylation of Chk2 in vivo by ataxia telangiectasia-mutated (ATM) on threonine 68 (T68) initiates a phosphorylation cascade that promotes the full activity of Chk2. We identified three serine residues (S19, S33, and S35) on Chk2 that became phosphorylated in vivo rapidly and exclusively in response to ionizing radiation (IR)-induced DNA double-strand breaks in an ATM- and Nbs1-dependent but ataxia telangiectasia- and Rad3-related-independent manner. Phosphorylation of these residues, restricted to the G(1) phase of the cell cycle, was induced by a higher dose of IR (>1 Gy) than that required for phosphorylation of T68 (0.25 Gy) and declined by 45 to 90 min, concomitant with a rise in Chk2 autophosphorylation. Compared to the wild-type form, Chk2 with alanine substitutions at S19, S33, and S35 (Chk2(S3A)) showed impaired dimerization, defective auto- and trans-phosphorylation activities, and reduced ability to promote degradation of Hdmx, a phosphorylation target of Chk2 and regulator of p53 activity. Besides, Chk2(S3A) failed to inhibit cell growth and, in response to IR, to arrest G(1)/S progression. These findings underscore the critical roles of S19, S33, and S35 and argue that these phosphoresidues may serve to fine-tune the ATM-dependent response of Chk2 to increasing amounts of DNA damage.